Ascending from the Abstract to the Concrete as a Principle of Expansive Learning - Engeström Y. (Moscow State University of Psychology and Education, 2020)
The article examines the potential of the dialectical principle of ascending from the abstract to the concrete for transforming practices of learning. It is shown that V.V. Davydov's work has created a foundation for such transformation. The theory of expansive learning builds on Davydov's legacy and brings the principle of ascending from the abstract to the concrete into learning and concept formation outside schools, "in the wild." Three studies investigating different scales of expansive learning are discussed, focusing on the internally contradictory germ cells discovered and used in those studies. The article concludes by emphasizing the need to integrate Davydov's revolutionary pedagogy and the broader agenda of school transformation as part of societal transformation.